Unusual Presentation in Infratentorial Superficial Siderosis: Acute Intracranial Hypertension - Maria Sheila Guimarães Rocha; Hugo Salomão Grangeiro Mirô; Gregori Manfroi; Arthur de Medeiros Dias; Raphaella Cardoso; Sonia Maria Dozzi Brucki (Case Reports in Neurology, 2021)
Superficial siderosis (SS) of the nervous system is a rare acquired condition related to hemosiderin deposits in subpial layers of the brain, brainstem, cerebellum, cranial nerves, and spinal cord, leading to brain iron-mediated neurodegeneration. The cardinal neurological features are slowly progressive hearing loss, ataxia, and pyramidal signs. Here we describe an atypical case of infratentorial SS evolving with acute intracranial hypertension in the absence of typical chronic signs.